E-participatory Approaches in Urban Design - Araf Oyku Turken; Engin Eyup Eyuboglu (Journal of Contemporary Urban Affairs, 2021)
The phenomenon of planning involving citizen’s participation in planning literature has been from the second half of the 20th century. Indeed, different methods and techniques have been used in the process. However, participatory practices are time-consuming and negotiations are tiresome. Accordingly, the integration of developing digital technologies into participatory processes has been seen as a potential to reach large audiences and provide time-space independence. Within the scope of this research, a detailed literature review was done regarding e-participation, and ten (10) examples representing the upper levels at the ladder of participation were examined within the context of the project, participation, and socio-technical criteria. SWOT analyzes were structured by grouping similar applications, and current trends for the use of e-participation in urban design have been revealed. The analysis showed that citizens e participation- participation tend to allow citizen design or location-based interaction, playful interfaces and game elements which can be sources for encouragement.